THE MEANING OF DIVERSION REGARDING THE PHILOSOPHICAL BASIS IN THE JUVENILE CRIMINAL JUSTICE SYSTEM - Darwanto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Talking about children is a very important thing, because children are a mandate and gift from God Almighty who have the dignity and honor as a whole human being, and play a role in determining the history of the nation, as well as a reflection of the nation's attitude in the future. Therefore, the state is obliged to provide protection and realize the welfare of children so that they can continue to live, to grow and develop according to their nature. Today, the impact of the rapid dynamics of life can change the characteristics of children where children are a hope for the nation and state for the future. However, in fact, children are rampant in committing a form of crime based on ignorance due to the surrounding environment. In Indonesia, children who commit crimes, especially children who are underage or not competent, receive a form of legal protection in the form of diversion. However, there are still many children who are in conflict with the law even though the child is underage or not competent, ending up undergoing criminal sanctions in the form of imprisonment for children. So with that, the provisions of the diversion policy can still be said to not fully reflect legal protection for children in conflict with the law, especially for children who are under age or legally incompetent. It is only right that the interests of children are fully protected for the future of the child through diversion